Methods of Reducing Fat Content in Ice Cream and their Influences on Flavor of Ice Cream - Yang, Yueyu (Transactions on Environment, Energy and Earth Sciences, 2024)
The increasing awareness of the health's importance leads to the increasing demand for healthy food. To meet the demand of the market, ice cream industries need to find applicable ways to make their ice cream healthier. Lowering the fat and sugar contents for ice cream are two main areas researchers can work on to achieve it. Researchers have already done great jobs in these aspects. Some sugar substitutes can even be used in daily cooking. However, the methods of fat reduction are not as known as the sugar ones. So this report will focus on the several methods that factories can use to reduce the fat content in the ice cream. The way that these methods reduce the fat content and what difference in flavor these methods will bring to the ice cream will be mainly discussed in this report. Due to the importance of the flavor of fat for ice cream flavor, this report also analyzes how these methods make a difference in the flavor of ice cream. It shows that all of these methods will not bring negative effects of the flavor of the ice cream under certain conditions. This report provides examples for further research of fat reduction methods for ice cream. The methods mentioned here more or less influence the flavor of the ice cream, and these methods are too general. Further research is needed in how to reduce the influence of flavor or finding a better way to achieve the fat reduction for a certain taste of ice cream.